Escravos artesãos: preço e família (Rio de Janeiro, 1789-1839) - Lima, Carlos A. M. (Estudos Econômicos (São Paulo), 2000)
This article compares prices of slave artisans and evaluations of slaves in general, men and women (Rio de Janeiro, 1789-1839). It deals with almost three hundred inventories of the estates of deceaseds, which contain evaluations related to more than three thousands slaves, including more than one thousand slaves trained as artisans. It also analyses information about slave families including artisans, as well as, through the questions mentioned above, the place of slave artisans in local economy and society.